(Lynette writing about) 'Nesta': Recollection, Reclamation and Reconstruction in Lynette Roberts's lost novel. (December 2018) - Hughes, Daniel
Abstract : This article furthers the nascent re-discovery of the Argentine-Welsh writer Lynette Roberts, whose poems returned to print in 2005. Written by Roberts in Llanybri, Carmarthenshire, during the 1940s, 'Nesta' is an unevenly experimental re-construction of the life of the Welsh medieval princess Nest ferch Rhys, and was read by figures such as Robert Graves and T.S. Eliot, who considered the novel for publication at Faber. This essay argues that the triple aims of 'Nesta' are as follows: to recollect the Welsh woman Nest ferch Rhys and the background of her life; to reclaim Nest from these male-dominated histories; and to ultimately reconstruct Nest as the character Nesta. In analysing this tripartite strategy, this article will demonstrate that Roberts's text uses the intersection between history and imaginative speculation to position Nest, in the form of the character Nesta, as a woman of national and historical significance.